Successful treatment modalities for missing lateral incisors- A systematic review - Nasser D. Alqahtani (Elsevier, 2021)
Background: Effective management of Missing lateral incisor has remained a challenge for the clinicians. A multi-disciplinary approach involving orthodontist, restorative dental specialist, pediatric dental specialist, periodontist, oral surgeon and general dentist has proved ideal. Our aim is to review the ultimate esthetic success, and long term survival results between the orthodontic and restorative management of missing lateral incisor. Materials and methods: Following the PRISMA guidelines, a systematic review of the published articles pertaining to the topic of interest was done. Searches were carried out in four different databases since February 2021 to April 2021. Results: A total of 580 references were found from searches conducted in PubMed, Scopus, Cochrane and Web of Science, and 19 articles were selected and analyzed fully, after screening the title and abstract, 6 articles were included for the study. Conclusion: An essential orthodontic space closure in combination with modern aesthetic prosthetic tooth replacement techniques has been reported to achieve greater success.